-7(1-p)=-2(1-3p)

Simple and best practice solution for -7(1-p)=-2(1-3p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(1-p)=-2(1-3p) equation:


Simplifying
-7(1 + -1p) = -2(1 + -3p)
(1 * -7 + -1p * -7) = -2(1 + -3p)
(-7 + 7p) = -2(1 + -3p)
-7 + 7p = (1 * -2 + -3p * -2)
-7 + 7p = (-2 + 6p)

Solving
-7 + 7p = -2 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
-7 + 7p + -6p = -2 + 6p + -6p

Combine like terms: 7p + -6p = 1p
-7 + 1p = -2 + 6p + -6p

Combine like terms: 6p + -6p = 0
-7 + 1p = -2 + 0
-7 + 1p = -2

Add '7' to each side of the equation.
-7 + 7 + 1p = -2 + 7

Combine like terms: -7 + 7 = 0
0 + 1p = -2 + 7
1p = -2 + 7

Combine like terms: -2 + 7 = 5
1p = 5

Divide each side by '1'.
p = 5

Simplifying
p = 5

See similar equations:

| (1/3h)-4((2/3h-3)=(2/3)h-6 | | -.01x+60=-200 | | c/2=3 | | 1.1y+6.21=4.78 | | 3-3y=9 | | 2+4y-3=11 | | u+192=-8u-6 | | x(5x-8)=333 | | 10-x-5x=4 | | 1.1+6.21=4.78 | | -10k=360 | | -10y+18=6(2c-12) | | -4a-3=a+222 | | 2x-16+5x=3x-7 | | 4/5×116 | | 6x^(2/3) | | g-196=-5g-4 | | =x^3+2x^2+4x+8 | | x-40+3x=56 | | 2.5=((x-2000)/2000)/-.30) | | A=10-2b | | 10x-2.25=7x | | 28x^2+186x+96=0 | | (6x)^2/3 | | -7-g=-49 | | -9e+8=e+448 | | 3(x*x)-32=16 | | -37+4x=7x+26 | | n/25=6 | | x^2+2(2k+5)x-(13k+4)=0 | | 7x-7-4x=31 | | X-8y+12=0 |

Equations solver categories